Measuring and Analyzing of the Relationship between the Financial Development, Economic growth, and Poverty in Iraq with the Autoregressive Distributed lag Model framework for the period (1980-2010) - العبدلي سعد عبد نجم; علي ازهار حسن (Journal of Economics and Administrative Sciences, 2014)
The developed financial system is essential for increasing economic growth and poverty reduction in the world. The financial development helps in poverty reduction indirectly via intermediate channel which is the economic growth. The financial development enhancing economic development through mobilization of savings and channel them to the most efficient uses with higher economic and social returns. In addition, the economic growth reduces the poverty through two channels. The first is direct by increasing the introduction factors held by poor and improve the situations into the sectors and areas where the poor live. The second is indirect through redistribution the realized incomes from the economic growth as well as the realized incomes from the government revenues which can be used to transfer the payments and improve the living standard which finally lead to reduce the poverty. By using the Autoregressive Distributed lag Model (ARDL) the paper found that there is significant causality from economic growth to poverty reduction and another one from inflation to the poverty reduction. However, the paper also found a weak nexus between financial development and poverty reduction . in addition, the financial development and economic growth do not play any significant role in reducing the poverty rate in Iraq. However, the econometrics analysis revealed that the inflation is the main factor effecting the poverty rate in the short and long run.